(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Noisy phone calls are aggravating and distracting, as well as frustrating. They may be classed as ’nuisance’, ’emergency’, ’random’, and ’unsolicited’ calls. Users have no inherent privileges on the internet; rather, their personalities are produced without any arrangement or evidence of involvement. It costs the U.S. communications company 8 billion per year to avoid call spam on the phone grid. Between January 2014 and June 2018, the FTC (Federal Trade Commission) received over 22 million reports of fraudulent and illegal telemarketing calls. Nowadays, the mobile network is used to issue automatic phone calls such as robocalls. Since it operates on text, we struggle with the following: What tactics and methods do we use to combat spam? Telephone TFD (Telecom Fraud Detection) here is discussed first. Concerning spam, we advanced our proposal by proposing a targeted traffic detection using a single weighted credibility algorithm with appropriate weighting criteria.